(untitled) (Journal of Laboratory Animal Science, 2024)
The establishments registered with the Committee for Control and Supervision of Experiments on Animals (CCSEA), Good Laboratory Practice (GLP) certified, and AAALACInternational accredited were obtained from online sources. The spatial distribution map of the establishments was prepared by collecting latitude and longitude using Quantum Geographic Information System (QGIS) version 3.4 Madeira, an open-source software. The establishments registered with CCSEA, GLP certified, and AAALAC accredited in India were 1583, 52, and 28, respectively and the period was confined to 1999 to 2023. Based on the organization nature, more private establishments were registered with CCSEA [1132], GLP [48], and AAALAC International [28] than Government establishments. The type of animals used for animal experiments by the establishments revealed that the small animals were in CCSEA [91.5%], GLP [68%], and AAALAC International [71%] compared to large animals. Based on the breeding purpose, establishments carrying in-house breeding were in CCSEA [79%], GLP [71%], and AAALAC International [70%]. The purpose of registration showed a higher number of establishments with educational purposes for CCSEA, and contract establishments for GLP and AAALAC International. The state-wise analysis revealed a higher number of establishments registered with CCSEA, GLP certified, and AAALAC International accredited were in Maharashtra, Telangana, and Maharashtra, respectively. The goals of CCSEA, GLP, and AAALACInternational are to enhance the animal well-being and quality of animal experiments, improve laboratory animal facility standards, and enhance biological research on humans and animals. Further, there is a need for a good monitoring system for the establishments involved in animal experiments in India.